Solar, wind and logistic substitution in global energy supply to 2050 – Barriers and implications. (January 2022) - Lowe, R.J.; Drummond, P.
Abstract: The sustained rapid growth and learning rates displayed by solar PV and wind electricity generation capacity over recent decades appear to be unprecedented. With these technologies now available at costs competitive with - or below - those of fossil fuel incumbents in many parts of the world, high rates of growth appear likely to continue. In this paper we use 'top-down' extrapolation of global trends and simple and transparent models to attempt to falsify the proposition that PV and wind have the potential to achieve dominance in global primary energy supply by 2050. We project future deployment of PV and wind using a logistic substitution model, and examine a series of potentially fundamental constraints that could inhibit continued growth. Adopting conservative assumptions, we find no insuperable constraints across physical and raw materials requirements, manufacturing capacity, energy balance (EROEI), system integration and macro-economic conditions, to this outcome. We also demonstrate synergy with direct air carbon capture and storage (DACCS) that would allow the achievement of global net-zero CO2 emissions by mid-century. Achieving such an outcome would require large scale reconfiguration of the architecture of global and regional energy systems, particularly from 2040 onwards. Low cost primary electricity is likely to be a significant factor in driving such a reorganisation. But given the speed and depth of the transition, hurdles will remain that will require foresight and strategic, coordinated action to overcome. Highlights: Extrapolating PV and wind deployment using logistic substitution suggests they may dominate global energy supply by 2050. There are synergies between PV and wind, and DACCS. DACCS adds flexibility to a renewably powered energy system. This supply-side transformation would both drive and require a wholesale reconfiguration of the rest of the energy system. With DACCS, this process could reduce net global CO2 emissions from energy to zero by 2050, and below zero thereafter. There appear to be no insuperable physical or economic barriers to such an outcome.